Динаміка чисельності бобра європейського (Castor fiber) малої річки Руда в межах НПП «Пирятинський» - Терех, Дарина; Подобайло, Анатолій Віталійович (Київський національний університет імені Тараса Шевченка, 2024)
The European beaver (Castor fiber) is the largest rodent that plays a significant role in water regulation in Ukraine. At the beginning of the XX century, the population of this species was endangered, but thanks to conservation activities, it gradually began to increase over the decade. Throughout our country, its activity can be seen again in aquatic ecosystems, where the European beaver plays an important role in regulating the water regime. For 7 years now, Pyriatynskyi National Park has been counting the number of beavers to understand the dynamics of the population development on the territory of the small Ruda River. In order to determine the dynamics of beaver honesty, a special description form was filled out to add data on each site and determine the number of individuals by the number of gnawed trees.
Population dynamics of the european beaver (Castor fiber) in the small Ruda river within the Pyriatynskyi NP